PENERAPAN BIMBINGAN GURU DALAM PROSES BELAJAR MENGAJAR DI SDLB - Musa Sukardi (Sekolah Dasar : Kajian Teori dan Praktik Pendidikan, 2013)
Abstract: Application of teachers’ guidance in teaching and learning process in special education elementary school. A guidance service is an integral part of all educational activities for special education elementary school students. This condition should be accompany with teachers’ competency in conducting a guidance so it can develop the potency of special needs children optimally. The application of guidance in the special education elementary school children’s teaching and learning process were studied from application of individual understanding function, channeling, adjustment, prevention, modification, and development. Research results at City of Malang and Region of Malang special education elementary school: (1) Teachers’ competency in applying guidance in teaching process on individual understanding function can be categorized good, (2) Teachers’ competency in applying guidance on teaching process in channeling and adaptive function can be categorized good, (3) Teachers’ competency in applying guidance in teaching process on self adjustment, prevention, modification, and self development function can be categorized good.Abstrak: Layanan bimbingan merupakan bagian integral dari keseluruhan kegiatan pendidikan pada anak SDLB. Kondisi ini perlu diiringi dengan kemampuan guru dalam melaksanakan program bimbingan agar dapat mengembangkan potensi anak berkebutuhan khusus seoptimal mungkin. Penerapan bimbingan dalam proses belajar mengajar anak SDLB dikaji dari penerapan fungsi pemahaman individu, penyaluran, penyesuaian, pencegahan, perbaikan, dan pengembangan. Hasil penelitian di SDLB Kota dan Kabupaten Malang: (1) kemampuan guru menerapkan bimbingan dalam proses belajar mengajar, pada fungsi pemahaman individu termasuk baik; (2) kemampuan guru menerapkan bimbingan pada fungsi penyaluran, dan fungsi adaptif termasuk baik; (3) kemampuan guru menerapkan bimbingan pada fungsi penyesuaian diri, fungsi pencegahan, perbaikan, dan fungsi pengembangan termasuk baik.Kata Kunci: kemampuan guru, bimbingan, proses belajar mengajar, anak SDLB